Improvement of Heat Sink Performance Using Graphite and Graphene Coating - Hadi, Ammar M.; Ismael, Muneer A.; Alhattab, Haider A. (Basrah Journal for Engineering Sciences, 2021)
This experimental research depicts the role of coating hot surfaces by graphite and graphene on the process of heat dissipation from these hot surfaces. Three aluminum specimens have been prepared for test, one of theme is coated by graphite, another one by graphene a while the third is left free of coating for comparison purpose. Each specimen is tested separately in a home-made wind tunnel. A plate electrical heater is adhered on the bottom of the specimen to simulate the generated energy by a heat sink. A heat sink composed of high thermal conductivity was applied between the heater plate and the base plate of heat sink to reduce the contact resistance to heat flow. The experiments are conducted with four turbulent Reynolds number. The results reveal that the sample coated by graphene exhibits the best thermal dissipation while the uncoated specimen shows the worst thermal performance.